Management of adolescent polycystic ovary syndrome - Morshed, Md Shahed; Banu, Hurjahan (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Polycystic ovary syndrome (PCOS) is a common adolescent problem and its prevalence is rapidly increasing worldwide. Diagnosis of PCOS during this period is difficult due to the overlapping of the diagnostic criteria with normal pubertal development. Currently, the International evidence-based guideline (2018) has recommended using the Rotterdam criteria excluding the polycystic ovarian morphology component. However, the definition of each component depends on the age of the menarche. Similarly, the treatment options are not adequately evidence-based, rather adopted mostly from adult guidelines. Due to several concerns, a combined oral contraceptive pill-sparing combination therapy (spironolactone+pioglitazone+ metformin= SPIOMET) might be a promising therapeutic option. Duration of treatment is another uncertain issue. Prospective studies as well as well-designed randomized controlled trials are required for adequate management of adolescent PCOS. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2022; 1 (2): 55-64